Pengaruh Deskripsi Kerja dan Kualifikasi Kerja terhadap Kompetensi Prajurit Korps Marinir - Hendrayana, Kankan; Triutomo, Gunawan; Herman, Juli (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Therefore, the purpose of this study is to analyze the influence of Job Descriptions partially on the Competence of Marine Corps soldiers, analyze the direct influence of Job Qualifications partially on the Competence of Marine Corps soldiers, analyze the influence of Job Descriptions and Job Qualifications simultaneously on the Competence of Marine Corps soldiers. In this study, to determine the sample, the researcher used a probability sampling technique, namely simple random sampling (sampling by Random/simple random) with a total of 393 respondents. The research method used in this study is quantitative with a survey technique. The data processing used in this study uses SPSS 27. The results of the study show that the job description variable is obtained at 6,098, the job qualification obtained is 19,348 greater than the t table which is 1,649 and the simultaneous influence is 1108,219 greater than the f table which is 2.63. The coefficient of determination value obtained was 85% while the remaining 15% was influenced by variables outside the research. The implications that can be given in this study as input for Pasmar 2 in improving the abilities of soldiers, honing the skills of soldiers to reduce difficulties in carrying out tasks and work capabilities to be optimal and as input for Pasmar 2 also by optimizing the job description and job qualifications of soldiers.